PENEGAKAN HUKUM PEMALSUAN DOKUMEN KEIMIGRASIAN OLEH WNA MENGACU PADA UU NO. 6/2011, STUDI PUTUSAN NO. 292/PID.SUS/2021/PN BTM: - Aden Alfiansyah; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2023)
This research examines the principles, legal norms, and concepts within the Immigration Law in Indonesia. It focuses on the case of document forgery by a foreign national, MYAT THIT alias MUHAMMAD, a Myanmar citizen in Batam. The defendant was arrested at Pantai Stress, Batu Ampar, for not having a Myanmar passport and residence permit. The research problem formulation is: What is the role of the immigration office in supervising Foreign Nationals in Batam? And how is the law enforced against immigration offenses committed by Myanmar citizens? The research method used is normative juridical, drawing conclusions through deductive logic. The research results reveal that the concept and mechanism of supervision over foreign nationals (FN) in Batam are still unclear and cannot be implemented effectively.